2023
DOI: 10.22190/fume201215042h
|View full text |Cite
|
Sign up to set email alerts
|

IMPROVEMENT OF SURFACE QUALITY OF Ti-6Al-4V ALLOY BY POWDER MIXED ELECTRICAL DISCHARGE MACHINING USING COPPER POWDER

Abstract: Electrical Discharge Machining (EDM) is one of the most popular non-conventional machining processes that are being used in many high precision manufacturing industries. To increase the EDM performance, a hybrid technique, namely, powder mixed electrical discharge machining (EDM) (PMEDM) is generally used for getting more precise requirements. In this study, an experimental investigation is carried out in order to explore the machining performance of the PMEDM process on Ti-6Al-4V alloy using copper (Cu) powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The importance of surface roughness in additive manufactured parts is greatly documented in scientific papers [22]. Dong et al [23] investigated how electrochemical polishing and chemical etching methods, used as post-process treatments, improve the surface finish of lattice structures made from Ti6Al4V manufactured with direct metal laser sintering (DMLS).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of surface roughness in additive manufactured parts is greatly documented in scientific papers [22]. Dong et al [23] investigated how electrochemical polishing and chemical etching methods, used as post-process treatments, improve the surface finish of lattice structures made from Ti6Al4V manufactured with direct metal laser sintering (DMLS).…”
Section: Introductionmentioning
confidence: 99%
“…A surface roughness of 3.29 µm was obtained at a machining combination of a 120 µs spark duration, an 8 A current, and a 40 µs spark-off duration. A few more important past attempts highlight the capabilities of electric discharge machining and its variants for machining stainless steel and titanium-type difficult-to-machine materials [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the PMEDM is suitable for machining MMCs with ceramic reinforcements. The PMEDM also improved the surface properties of MMCs.Haque et al [18] investigated the effect of Cu powder concentration on PMEDM machining of Ti-6Al-4V alloy. The results indicated that the Cu powder concentration has a positive effect on the surface finish till an optimum value of 4 g l −1 .…”
Section: Introductionmentioning
confidence: 99%